Effect of Kochia (Kochia scoparia) Interference on Sunflower (Helianthus annuus) Yield. Issue 1 (March 2014) - Lewis, Derek W.; Gulden, Robert H.
Abstract : Kochia is a weed found in many sunflower fields across the Northern Great Plains. There is limited information about the ability of sunflower plants to compete with kochia, specifically when the weed grows both in the crop row and in the inter-row space, as in zero tillage systems that rely solely on herbicides to manage weeds. An experiment was conducted over seven site–yr, from 2009 to 2011, to determine the effect of kochia density and relative time of kochia seedling recruitment on sunflower growth and development, yield and seed quality. Kochia seed was broadcast on the soil surface at six densities, into sunflowers planted in 75-cm rows, either at the same time as the sunflower crop was planted (early weed seedling recruitment), or when the sunflowers were at the four-leaf stage (late weed seedling recruitment). When kochia plants emerged at the same time as the sunflowers, yield was reduced by up to 76% and sunflower head diam was reduced in four site–yr, stem diam was reduced in three site–yr, height was reduced in two site–yr and the number of leaves per sunflower plant was reduced in two site–yr The 5% action threshold for early emerging kochia was four kochia plants m −2 in the combined site–yr analysis. Additionally, early recruiting kochia seedlings reduced sunflower seed size and seed weight at two and three site–yr, respectively. Kochia plants that emerged after the four-leaf stage of the sunflower crop did not affect sunflower growth and development, yield, or seed quality. To reduce the potential for yield and seed quality losses, sunflower growers should be proactive with respect to managing kochia in sunflowers, particularly when the kochia plants emerge at about the same time as the sunflowers.